Difficulty of Teachers in Developing School-Based Self-Learning Modules: Basis for I’m Assertive, Motivated to Focus Guro Development (iAM-FGD) Program - Joan Minerales; Roy Tribunalo; George Jagunos (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aimed to develop intervention program based on teachers’ level of difficulty in developing school-based Self-Learning Modules (SLMs) among thirty-eight teachers of Glan-Padidu National High School, SY 2020-2021. It utilized correlational quantitative and qualitative research designs. Results revealed that respondents have difficulty in developing school-based SLMs in content with 2.228 composite mean: variation of teaching methods and learning activities with 1.763 weighted mean; presentation with 2.535; assessment with 2.544; and language with 2.579. Furthermore, there is a significant relationship between educational attainment and language with negative correlation – the lower the educational attainment of teachers, the higher the level of difficulty experienced. Hence, teachers are encouraged to pursue graduate studies. The I’m Assertive, Motivated to Focus Guro Development (iAM-FGD) Program was conducted to enhance the knowledge, skills, and attitude among teachers who experienced difficulties in developing school-based SLMs. Focused group discussion by learning area was held. Teachers prepared a lesson plan from their developed school-based SLMS. They presented and defended why they used such teaching strategies and learning activities. Technical assistance was provided by instructional coaches. Fellow teachers shared insights on: “What specific learning activity and teaching strategy is worth emulating?”.